1 7/18 + х = 5 2/3 - 3 5/9
1 7/18 + х = 5 6/9 - 3 5/9
1 7/18 + х = 2 1/9
х = 2 1/9 - 1 7/18
х = 2 2/18 - 1 7/18
х = 1 20/18 - 1 7/18
х = 13/18
- - - - - - - - - - - - - - - - - - - -
25/18 + х = 17/3 - 32/9
Приводим обе части уравнения к общему знаменателю 18
25 + 18х = 102 - 64
25 + 18х = 38
18х = 38 - 25
18х = 13
х = 13 : 18
ответ: 13/18.
1 7/18 + х = 5 2/3 - 3 5/9
1 7/18 + х = 5 6/9 - 3 5/9
1 7/18 + х = 2 1/9
х = 2 1/9 - 1 7/18
х = 2 2/18 - 1 7/18
х = 1 20/18 - 1 7/18
х = 13/18
- - - - - - - - - - - - - - - - - - - -
1 7/18 + х = 5 2/3 - 3 5/9
25/18 + х = 17/3 - 32/9
Приводим обе части уравнения к общему знаменателю 18
25 + 18х = 102 - 64
25 + 18х = 38
18х = 38 - 25
18х = 13
х = 13 : 18
х = 13/18
ответ: 13/18.